In vitro assay and in vivo effect of artemisinin in Trypanosoma brucei brucei-infected Wistar rats - Kelvin Olutimilehin Jolayemi; Mohammed Mamman; Dahiru Sani; Magdalene Ogbonneya Okoronkwo; Abubakar Usman; Collins Chimezie Udechukwu; Joshua Seyi Oyetunde (Elsevier, 2021)
Background: Control of the trypanosomosis has been targeted towards vector control or by the use of antitrypanosomal drugs such as diminazene aceturate and isometamidium with reports of toxicity and relapse following treatment. Hence, the need for continuous research for a safe, efficacious and less toxic drug. In previous studies, artemisinin has shown antitrypanosomal effects against Trypanosoma brucei rhodesiense and also against Trypanosoma brucei brucei (T. b. brucei) in vitro. This period of drug repurposing has led to scientists searching for ways of utilising artemisinin because of its reported multifunctionality and ability to mediate several targets that are important for different diseases. Purpose: To evaluate the in vivo effects of artemisinin against T. b. brucei following the in vitro assay. Methods: Previously to perform the in vivo assays, the in vitro effects of artemisinin on the T. b. brucei trypomastigotes growth were assessed. The in vivo effects were tested on Wistar rats at doses 5 mg/kg and 10 mg/kg, respectively. All Wistar rats were euthanised at the end of the experiment; kidney, lung, liver and brain samples were harvested and processed for histopathological examination. Results: Complete cessation (p < 0.001) of trypanosomal motility in vitro by 2 and 20 µg/µl artemisinin between 10  to 60 min was observed when compared to the controls. Artemisinin showed an IC50 value of 0.42 µg/µl while the positive control drug diminazene aceturate displayed a lower activity with IC50 of 2.99 µg/µl. Level of parasitaemia and survival rate showed significant differences (p < 0.05) in treated groups compared to group II (Infected and untreated). Mean packed cell volume, haemoglobin concentration, mean corpuscular volume and mean corpuscular haemoglobin concentration decreased significantly (p < 0.05) in all infected groups and returned to almost pre-infection values following treatment. Histopathological evaluation showed artemisinin to prevent the distortion of normal architecture of the selected organs. Conclusions: In vitro, artemisinin produced a complete inhibition of T. b. brucei motility at 2 and 20 µg/µl. In vivo, artemisinin at 5 and 10 mg/kg prevented histoarchitecture damage of selected organs and caused an elevated haematological profile.